Skin nerve phosphorylated α-synuclein deposits in Parkinson's disease with orthostatic hypotension. Issue 1 (January 2019) - Donadio, V.; Incensi, A.; Del Sorbo, F.; Rizzo, G.; Infante, R.; Scaglione, C.; Modugno, N.; Fileccia, E.; Elia, A.E.; Cencini, F.; Liguori, R.
Abstract : To investigate phosphorylated α -synuclein (p-syn) deposits in skin nerves of Parkinson's disease (PD) patients with neurogenic orthostatic hypotension (OH) and a PD matched group without dysautonomia. We enrolled 28 idiopathic PD patients with abnormal nigro-striatal DatScan and cardiac MIBG: (1) 14 of them complained of neurogenic OH (PD + OH); and (2) 14 matched patients did not complain of autonomic dysfunctions (PD-OH); 7 of them were re-evaluated over a follow-up (4 ± 2 years). Patients underwent skin biopsy in proximal (i.e. C7 paravertebral spine region) and distal (i.e. thigh and leg) sites. PD + OH showed a higher p-syn deposition than PD-OH with a widespread autonomic cholinergic and adrenergic skin nerves involvement. Over the follow-up PD-OH patients showed a marked increase in motor dysfunctions scores without autonomic symptoms and a slight increase of skin p-syn deposition but still lower than PD + OH. PD + OH showed a wide involvement of p-syn deposits in autonomic cholinergic and adrenergic skin nerves skin; (2) PD-OH showed a lower load of skin p-syn mainly restricted to adrenergic fibers of skin vessels, still persisting over a follow-up. These data supported a different pathogenesis between PD + OH and PD-OH and may help to identify a specific diagnostic trait for PD + OH patients.